Contemporary Climate Movements: Ecological Radicalism, Extremism, or a New Wave of (Eco)Terrorism? A Case Study of Just Stop Oil and Letzte Generation Organizations - Adamczyk, Marcin; Siekierka, Michał (Historia i Polityka, 2025)
In today’s world, among other environmental issues, the problems of anthropogenic climate change and the fear of a “climate catastrophe” have been the central focus of contemporary discourse. This has compelled most governments to make efforts to reduce the use of fossil fuels in the energy industry and beyond. Information about the rapid pace of climate warming has simultaneously become a source of social unrest and radicalization. This is evident in popularising movements such as Fridays for Future, Youth for Climate, Climate Strike, Youth Strike for Climate, Extinction Rebellion, etc. One of their key demands is the virtually immediate and drastic reduction of greenhouse gas emissions by all countries worldwide. In their efforts to promote their agenda, these organizations are increasingly resorting to methods reminiscent of the history of extreme environmental movements. These methods include blocking transportation and transmission infrastructure or engaging in increasingly bold attempts to destroy property, including unique works of art. In this article, as a case study, we will explore the activities of two organizations, Just Stop Oil (JSO) and Letzte Generation (LG), to determine whether the activities of contemporary pro-environmental movements exhibit signs of radicalism or environmental extremism. Additionally, we will examine whether their actions can be considered analogous to ecoterrorist actions of the past. As part of our research, in addition to the case study, we also utilized the desk research method. We analyzed academic publications on extremism and terrorism and used the content of the JSO and LG websites as well as media reports on their current activities as source material.